MON-921 Autonomous Cortisol Secretion Coexisting with Pancreatic Neuroendocrine Tumor: A Rare Presentation - Faro, Fernanda (J Endocr Soc, 2020)
Introduction: neuroendocrine tumors (NET) are a very rare and heterogeneous group of malignancies that can be associated with adrenocortical tumors in approximately 20% of the cases, mostly bilateral and non-functioning. Autonomous cortisol secretion occurs in less than 10% of adrenal incidentalomas and the coexistence of pancreatic neuroendocrine neoplasms and autonomous cortisol secretion is not well-described. Clinical case: a 54-year-old man with previous history of systemic hypertension and type 2 diabetes mellitus, presented with left hypochondrium pain in the last 18 months, associated with abdominal distension, constipation and nausea. Physical examination without abnormalities. Abdominal tomography demonstrated dilatated pancreatic duct and a solid heterogeneous nodule in left adrenal, measuring about 2.7 cm. Ecoendoscopy revealed a heterogeneous, hypoechoic and oval nodular lesion, located at the transition of pancreatic head and uncinate process, measuring 1.5x1.1cm. Biopsy was performed, showing a pattern of neuroendocrine neoplasia, with chromogranin and synaptophysin +, Ki67 1%. Gallium-68 dotatate PET revealed two pancreatic nodular formations, one in proximal neck/body (1.5 cm) and the other in pancreatic tail (1 cm), presenting SUV of 20.4 and 21, respectively. Adrenal nodule presented minimal increase in radiopharmaceutical concentration. To exclude the hypothesis of metastasis, PET FDG was performed, showing physiological uptake in adrenal nodule. Pituitary MRI had no abnormalities. Chromogranin A and gastrin values were normal. Pheochromocytoma and primary hyperaldosteronism were excluded. Hypercortisolism investigation presented the following results: 23h salivary cortisol 167ng/dl (NR < 100), 24-hour free urinary cortisol 42.1 mcg/24h (NR 4.2-60), post-1mg and 2mg dexamethasone serum cortisol of 10.8 mcg/dl and 3.8 respectively (serum dexamethasone levels of 193 and 780 ng/dl; NR > 130), ACTH 13 and 11 pg/ml. By these results, coexistence of non-functioning pancreatic neuroendocrine tumor and autonomous cortisol secretion was confirmed. A total pancreatectomy with partial gastrectomy and bileodigestive anastomosis was performed. Pathological anatomical evidence demonstrated a well-differentiated neuroendocrine tumor (NET G1) and immunohistochemistry analyses showed positive chromogranine A, synaptophysine, Ki67 1% and negative ACTH. Clinical follow-up of the adrenal adenoma was preferred. Conclusion: although most adrenocortical tumors associated with NET are nonfunctional, hypercortisolism should be considered. Adrenal metastasis and ectopic ACTH secretion are differential diagnosis. Clinical follow-up is an option when patient is asymptomatic and comorbidities are well-controlled.